(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
The relation between culture and television is usually appears like troubled and even impossible. In this article a historical revision is done to the presence of cultural contents in the public Spanish television, TVE, both national and regional, to defend the need of the presence of cultural spaces in television.